2017
DOI: 10.21037/tlcr.2017.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Spread through air spaces (STAS): a comprehensive update

Abstract: Abstract:The new concept of spread through air spaces (STAS) was introduced for pulmonary adenocarcinomas (ADC) in the 2015 World Health Organization (WHO) classification for lung cancer.Yet available data demonstrate that STAS is of high prognostic impact and associated with specific clinicpathological characteristics. This article provides a comprehensive overview on recent developments in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
1
50
0
1
Order By: Relevance
“…Spread through air spaces (STAS) is a recently recognized invasive pattern of lung cancer, defined as "micropapillary clusters, solid nests or single cells beyond the edge of the tumor into air spaces." 5 Although first introduced by Kadota et al in 2015, 6 similar concepts, including aerogenous spread with floating cancer cell clusters and tumor islands, have been reported. [7][8][9] Although the definite mechanisms of STAS have yet to be elucidated, several studies have shown an association with male gender, a history of smoking, and clinicopathologically invasive features, such as larger tumor diameter, the presence of pleural invasion, and histologically invasive types.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Spread through air spaces (STAS) is a recently recognized invasive pattern of lung cancer, defined as "micropapillary clusters, solid nests or single cells beyond the edge of the tumor into air spaces." 5 Although first introduced by Kadota et al in 2015, 6 similar concepts, including aerogenous spread with floating cancer cell clusters and tumor islands, have been reported. [7][8][9] Although the definite mechanisms of STAS have yet to be elucidated, several studies have shown an association with male gender, a history of smoking, and clinicopathologically invasive features, such as larger tumor diameter, the presence of pleural invasion, and histologically invasive types.…”
Section: Introductionmentioning
confidence: 92%
“…Spread through air spaces (STAS) is a recently recognized invasive pattern of lung cancer, defined as “micropapillary clusters, solid nests or single cells beyond the edge of the tumor into air spaces.” Although first introduced by Kadota et al . in 2015, similar concepts, including aerogenous spread with floating cancer cell clusters and tumor islands, have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…The histopathologic evaluation of lung cancer resection specimens involves assessment of tumor features with prognostic significance, such as lymphovascular invasion or pleural invasion. Recent studies have highlighted the significance of a new pattern of tumor spread in lung carcinomas, referred to as tumor spread through air spaces (STAS) . STAS was formally introduced in the 2015 World Health Organization classification for pulmonary carcinomas, which defined STAS as tumor cells present singly or in micropapillations, clusters, or solid nests within alveolar spaces of the lung parenchyma beyond the main tumor edge .…”
Section: Introductionmentioning
confidence: 99%
“…[2,3]The conception of STAS was rst introduced into our vision by Kadota and colleagues in 2015 [4].In the 2015 World Health Organization(WHO) Classi cation [5], STAS was newly recognized as a pattern of tumor spread in lung adenocarcinoma. STAS is de ned as micropapillary clusters, solid nests, or single cells spreading within air spaces beyond the edge of the main tumor [6]. STAS can be found in 14.8 to 56.4% of lung adenocarcinomas and has been proven to be a risk factor for survival and reoccurrence after operation [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%